Inattention over time-on-task: the role of motivation in mitigating temporal increases in media multitasking - Drody, Allison C.; Pereira, Effie J.; Danckert, James; Smilek, Daniel (Frontiers in Cognition, 2025)
IntroductionNumerous studies have demonstrated that attention and performance decline with time-on-task. In modern contexts, this gradual fading of attention can manifest as increases in media multitasking over time. Across two studies, we investigated whether increasing individuals' motivation to perform well on a task mitigates temporal increases in media multitasking.MethodStudy 1 re-analyzed data from a previously published study which provided participants with standard or motivating instructions before having them complete a sustained attention task with the option to media multitask. Study 2 extended this work by critically assessing in-the-moment motivation through thought probes throughout the task.ResultsIn both studies, media multitasking and corresponding decreases in task performance over time were attenuated as a function of increased motivation. Moreover, results from Study 2 revealed that motivation decreased with time-on-task for both groups; however, this decline was more gradual in the motivated group.DiscussionOur findings suggest that increasing the value individuals assign to attending to their current task may aid in prolonging sustained attention. These findings align with recent theories of vigilance that attribute temporal decrements in attention and performance to varying cost-benefit analyses rather than a depletion of resources over time.